2014
DOI: 10.4012/dmj.2014-100
|View full text |Cite
|
Sign up to set email alerts
|

Retention of crowns cemented on implant abutments with temporary cements

Abstract: This study was to examine the retentive force of crowns to implant abutments with commercial temporary cements. Six different temporary cements were investigated. Cast crowns were cemented to the abutments using each cement and their retentive forces to abutments were determined 7 or 28 days after cementing (n=10). The retentive force of the cements to abutments varied widely among the products [27-109 N (7-day), 18-80 N (28-days)]. The retentive force of all the cements was not reduced as the time elapsed, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
0
10
1
Order By: Relevance
“…Although calcium hydroxide-based cements have been used as temporary luting agents (7,10), there is little information available in the literature correlating its mechanical properties and retention. However, it has been suggested that mechanical strength of commercial luting agents could not be a predicting factor for crown retention to implant abutments (11). Further studies are required to help understanding the luting agent's behavior.…”
Section: Fit and Cementation Of Provisional Crownsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although calcium hydroxide-based cements have been used as temporary luting agents (7,10), there is little information available in the literature correlating its mechanical properties and retention. However, it has been suggested that mechanical strength of commercial luting agents could not be a predicting factor for crown retention to implant abutments (11). Further studies are required to help understanding the luting agent's behavior.…”
Section: Fit and Cementation Of Provisional Crownsmentioning
confidence: 99%
“…Multiple factors in oral environment such as temperature change, pH and occlusal forces affect properties and retention of provisional luting agents (6). Several studies reported the use of non-eugenol zinc oxide and calcium hydroxidebased luting agents in the clinical practice for temporary cementation of implant-supported crowns (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…In order to satisfy these requirements, temporary cements can be favorably used for this type of implant prosthesis. 4 The aim of this in vitro study was to evaluate the effect of two temporary crown cements (Resin based cement and Eugenol Free Zinc oxide cement) on the retention of two titanium implant supported crowns made of (Polymer infiltrated hybrid glass ceramic and Yttrium stabilized tetragonal zirconia).…”
mentioning
confidence: 99%
“…However, insufficient retention and frequent decementation of the restoration are common consequences when a provisional cement is used . In addition to the tensile strength of the cement, retention is influenced by other factors such as axial wall tapering, surface roughness, and height and width of the abutment …”
mentioning
confidence: 99%
“…13 In addition to the tensile strength of the cement, retention is influenced by other factors such as axial wall tapering, surface roughness, and height and width of the abutment. 7,9,13 Different techniques have been proposed to reduce the amount of excess cement extruded at the margin of cemented implant restorations, including venting and reducing the amount of loaded cement in the crown. 10,12,14,15 However, the effects of such techniques on retention of the crowns are not clearly understood.…”
mentioning
confidence: 99%